Distant Asian neighbours Japan and South Asia - Jain, Purnendra (New Delhi Sterling, 1996)
Contributed research papers.
Includes bibliographical references (p. [224]-225) and index.
Keywords: Japan -- Foreign relations -- South Asia; South Asia -- Foreign relations -- Japan; Japan -- Foreign economic relations -- South Asia; South Asia -- Foreign economic relations -- Japan